Modern trends in the management and increasing the competitiveness of industrial cluster associations in Russia - L. A. Akhmetov; D. V. Skvirya (Путеводитель предпринимателя, 2020)
The article discusses the issues and problems in the functioning of the cluster through the establishment of cooperative and mutually beneficial relations between contractors, suppliers of technologies and resources, related enterprises and the enterprises-manufacturers of raw materials for the organizations included in the cluster.